APLIKASI RENTAL MOBIL TRAVEL BERBASIS ONLINE PADA NUSA TRIP TRAVEL - Mochamad Yusuf Romdoni; Ahmad Fatoni; Ahmad Surahmat; Tauffik Qurohman; Masum Masum (Jurnal Sistem Informasi dan Informatika (Simika), 2025)
The aim of this research is to build an online travel application at PT. Nusa Trip Travel, which is intended for tourism and travel bureau companies to serve travel customer requests and can provide travel and tourism information. The presence of this application will be very helpful in serving every ticket ordering transaction carried out by customers wherever they are without having to go to a service bureau. This travel application will be built on an online basis where customers can see information on departure schedules, travel departure routes, rates and payments. The payment system implemented with this application requires customers to carry out a transfer process according to the total bill via a bank account. Payment will be declared successful by the admin if the payment matches the cost of the travel booking. The financial reports received will be detailed and clear with the aim of making each report easier so that all work will be easier to complete, especially in serving travel consumers, monitoring travel and other administration. This application was developed using the PHP programming language, the Codeigniter framework, which has been tested in web-based software development. Meanwhile, the system flow design here uses Unified Modeling Language (UML). This research uses a waterfall method approach in developing the system and the results of this research are expected to be able to help companies serve each customer more quickly, effectively and efficiently.